Utilization of Fermented Solution (Ensiling) from Brassica juncea as a Natural Preservative on Sardinella longiceps - Humairah Fitria; Safrida Safrida; Khairil Khairil (Universitas Syiah Kuala, 2020)
Ensiling from mustard green is a natural preservation method with a fermentation method with the aim of being a place for the development of lactic acid bacteria that can reduce pH to maintain an acidic atmosphere so that it inhibits the development of spoilage bacteria. The purpose of this study was to determine the effect of green mustard solution on the natural preservation of dencis fish and the organoleptic quality found in dencis fish. The benefit of this research is that it can provide information about the use of green mustard greens as a natural preservative of fresh dencis fish to the public. The method used in this study is an experimental method with a Completely Randomized Design (CRD) consisting of 4 treatments and 5 replications. The treatments were without immersion (P0), 1-hour immersion (P1), 3-hour immersion (P2), and 6-hour immersion (P3). Data analysis with Analysis of Variance (ANAVA) with further testing BJND at α = 0.05. The provision of green mustard solvent solution greatly affects the organoleptic (taste, color, texture and aroma) and greatly influences the level of panelists’ preference for aroma, texture and taste but does not look different in the color of fried dencis fish.